Development of an Interactive Digital Physics Module (IDMP) on the Concept of Global Warming to improve students' Problem Solving Skills - Fajrin, Virgiani Pangestika; Wibowo, Firmanul Catur; Nasbey, Hadi; Bunyamin, Muhammad Abd Hadi; Khamis, Noorzana Binti (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
Problem Solving Skills (PSS) are essential skills in life because they help students find creative and innovative solutions to various complex problems. Apart from that, global warming is one of the physics materials studied in Phase E of the Independent Curriculum. Through learning with the Interactive Digital Physics Module (IDMP), students can learn scientific principles and concepts to solve problems. However, so far physics learning has focused more on physics products, while aspects of scientific processes and attitudes that should be trained are often neglected. The aim of this research is the development of an interactive digital physics module (IDMP) on the concept of global warming to improve students' problem solving skills. This research method uses the ADDIE model with a total sample of 37 consisting of 10 males and 27 females regarding the problem solving skills of students in one of the schools in Banten Province, Indonesia. The results of the research show that the characteristics of the IDMP on the concept of global warming for student learning and the Problem Solving Skills test consisting of 4 indicators Clearly defining the problem increased by 0.71, Developing a plan of action increased by 0.72, the effectively implementing the plan indicator increased by 0.63 and the valuing indicator and reflecting on the outcome increased by 0.65 category. The average N-gain result of these four indicators is 0.69, meaning that students' problem solving skills have increased in the moderate category.